Retribution against collaborators of the occupiers after the end of the Second World War - Čoh Kladnik, Mateja (Studia Historica Slovenica, 2021)
Courts of national honour were established in some European countries after the end of the Second World War. These were special courts which assisted in the process of "cleansing" or the process of post-war retribution against collaborators of the occupiers. The author presents the criminal procedures for acts against national honour in Czechoslovakia, Croatia, Slovenia and Serbia. The courts of national honour assumed the role of revolutionary courts and through their operation contributed to the final seizure and consolidation of the Communist Party's power. They participated in the process of changing the socio-economic structure of the state. Trials before the courts of national honour violated one of the fundamental legal principles – nullum crimen sine lege: acts (the collaboration with the occupier) tried by the courts of national honour were not considered crimes at the time that they were committed.
Keywords: 1945; collaboration; confiscation of property; courts of national honour; Croatia; Czechoslovakia; Češkoslovaška; forced labour; Hrvaška; kolaboracionizem; occupation; povojni sodni procesi; prisilno delo; retribution against collaborators of the occupier; Second World War; Serbia; Slovenia; Slovenija; Srbija; svetovna vojna 1939-1945; trials; zaplemba premoženja